Pemikiran Bunuh Diri: Studi Fenomenologi pada Remaja Perempuan di Kabupaten Tana Toraja - Nugraha, El-Shaddai; Zainuddin, Kurniati; Kusuma, Perdana (Universitas Negeri Makassar, 2025)
Suicide is one of the biggest causes of death in teenagers, especially in Tana Toraja Regency. Suicide can occur due to previous suicidal thoughts. Suicidal thoughts are a desire to die that has not been accompanied by concrete action. Even though it is not accompanied by concrete action, it still needs to be given special attention so that it does not develop into a suicide attempt. This research aims to find out what the experience of having suicidal thoughts is and how suicidal thoughts are described in adolescent girls in Tana Toraja Regency. This research uses a qualitative method with a phenomenological approach. The respondents in this study were 3 people aged 17, 18 and 21 years. Data collection techniques used semi-structured interviews. The results of data analysis show that respondents' thoughts of suicide are based on different experiences, such as the death of parents, parental quarrels, violence in the family, and the influence of posts about suicide on social media. The feelings that respondents felt when they had suicidal thoughts were despair, loss of motivation and enthusiasm. The frequency of suicidal thoughts among respondents also varied, ranging from lasting for weeks, months, or even years. Respondents' descriptions of suicidal thoughts included cutting their veins, hanging themselves, and consuming dangerous chemicals. The description of suicidal thoughts was inspired by social media, suicide incidents in the neighborhood, and a family member's history of suicide attempts. The implication of this research is that it can be a reference for taking preventive action for teenagers who have suicidal thoughts so that they do not develop into suicide attempts, especially for teenage girls.